The Influence of the Brazil Cost in the Direct Investments in the Country from 2012 to 2018 (Global Journal of Management and Business Research, 2019)
Abstract not found
Keywords: brazil cost; direct investments; dynamic model averages; bayesian DMA method; brazilian infrastructure